The Xander ligament? Caution advised when using online encyclopaedias. Issue 2 (7th April 2020) - Ledger, Thomas; Toftness, Alexander
Abstract : Here, we discuss a series of events that led to an article in a prestigious medical journal mistakenly using a fake eponymous term that originated in a YouTube video and then spread to Wikipedia. The term has also spread to other places. In this digital world of fake news, open resources should be read discerningly in order to verify their contents.